GENETIC VARIATION OF AEDES AEGYPTI (DIPTERA : CULICIDAE) BASED ON DNA POLYMORPHISM - Rike Oktarianti; Sri Mumpuni (UPT Penerbitan Universitas Jember, 2016)
Dengue hemorrhagic fever (DHF) is a health problem in Indonesia, particularly in Jember. Dengue is a disease caused by Dengue virus (DENV). Ae. aegypti is the main vector for transmission of Dengue viruses into human. The spread of Dengue virus caused by the vector density. The objective of this research is to study the genetic variation of Aedes aegypti based on DNA polymorphism by Random Amplified Polymorphic (RAPD) PCR analysis. The mosquitoes were collected from Arjasa, Mumbulsari and Mayang in Jember district. The primer were used to RAPD analysis are OPE 16, OPE 17, OPE 19, OPF 2, OPF 4 and OPF 6. The result showed, the genetic variation of Aedes aegypti from Arjasa, Mumbulsari and Mayang based on DNA polymorphism were 22.58%, 23.53% and 21.21% respectively.